Myocardial Inflammation, Measured Using 18‐Fluorodeoxyglucose Positron Emission Tomography With Computed Tomography, Is Associated With Disease Activity in Rheumatoid Arthritis. Issue 4 (28th February 2019) - Amigues, Isabelle; Tugcu, Aylin; Russo, Cesare; Giles, Jon T.; Morgenstein, Rachelle; Zartoshti, Afshin; Schulze, Christian; Flores, Raul; Bokhari, Sabahat; Bathon, Joan M.
Abstract : Objective: To determine the prevalence and correlates of subclinical myocardial inflammation in patients with rheumatoid arthritis (RA). Methods: RA patients (n = 119) without known cardiovascular disease underwent cardiac 18‐fluorodeoxyglucose (FDG) positron emission tomography with computed tomography (PET‐CT). Myocardial FDG uptake was assessed visually and measured quantitatively as the standardized uptake value (SUV). Multivariable linear regression was used to assess the associations of patient characteristics with myocardial SUVs. A subset of RA patients who had to escalate their disease‐modifying antirheumatic drug (DMARD) therapy (n = 8) underwent a second FDG PET‐CT scan after 6 months, to assess treatment‐associated changes in myocardial FDG uptake. Results: Visually assessed FDG uptake was observed in 46 (39%) of the 119 RA patients, and 21 patients (18%) had abnormal quantitatively assessed myocardial FDG uptake (i.e., mean of the mean SUV [SUVmean ] ≥3.10 units; defined as 2 SD above the value in a reference group of 27 non‐RA subjects). The SUVmean was 31% higher in patients with a Clinical Disease Activity Index (CDAI) score of ≥10 (moderate‐to‐high disease activity) as compared with those with lower CDAI scores (low disease activity or remission) ( P = 0.005), after adjustment for potential confounders. The adjusted SUVmean was 26% lower among those treated with a non–tumor necrosis factor–targeted biologic agent compared with those treated with conventional (nonbiologic) DMARDs ( P = 0.029). In the longitudinal substudy, the myocardial SUVmean decreased from 4.50 units to 2.30 units over 6 months, which paralleled the decrease in the mean CDAI from a score of 23 to a score of 12. Conclusion: Subclinical myocardial inflammation is frequent in patients with RA, is associated with RA disease activity, and may decrease with RA therapy. Future longitudinal studies will be required to assess whether reduction in myocardial inflammation will reduce heart failure risk in RA.